2014
DOI: 10.5194/bg-11-347-2014
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of CO<sub>2</sub> exchange with an automated chamber system throughout the year: challenges in measuring night-time respiration on porous peat soil

Abstract: Abstract. We built an automatic chamber system to measure greenhouse gas (GHG) exchange in forested peatland ecosystems. We aimed to build a system robust enough which would work throughout the year and could measure through a changing snowpack in addition to producing annual GHG fluxes by integrating the measurements without the need of using models. The system worked rather well throughout the year, but it was not service free. Gap filling of data was still necessary. We observed problems in carbon dioxide … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
63
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 32 publications
5
63
0
Order By: Relevance
“…The reason is the higher temporal resolution of AC-derived C budgets, displaying daily C losses and gains. Observed crop-dependent differences in NECB are in accordance with Kutsch et al (2010), Jans et al (2010), Hollinger et al (2005) and Verma et al (2005), for example, who reported comparable EC-derived C balances for, inter alia, maize, sorghum and alfalfa.…”
Section: Plausibility Of Observed Socsupporting
confidence: 83%
See 3 more Smart Citations
“…The reason is the higher temporal resolution of AC-derived C budgets, displaying daily C losses and gains. Observed crop-dependent differences in NECB are in accordance with Kutsch et al (2010), Jans et al (2010), Hollinger et al (2005) and Verma et al (2005), for example, who reported comparable EC-derived C balances for, inter alia, maize, sorghum and alfalfa.…”
Section: Plausibility Of Observed Socsupporting
confidence: 83%
“…As a result, sensitive measurement techniques are required to precisely assess short-term temporal and small-scale (10-30 m) spatial dynamics in SOC (Batjes and van Wesemael, 2015). To date, the assessment of SOC has typically been based on two methods, namely (i) destructive, repeated soil inventories through soil resampling and (ii) non-destructive determination of net ecosystem C balance (NCEB) by measurements of gaseous C exchange, C import and C export (Leifeld et al, 2011;Smith et al, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…eddy covariance (EC) measurements), allow for high-temporal-resolution records of CH 4 emissions (Schrier-Uijl et al, 2011;Wille et al, 2008). Recently, a growing number of experimental GHG studies have employed automatic chambers (ACs) (Koskinen et al, 2014;Lai et al, 2014;Ramos et al, 2006), which can provide flux data with an enhanced temporal resolution and capture short-term temporal (e.g. diurnal) dynamics.…”
Section: Introductionmentioning
confidence: 99%